1996
DOI: 10.1073/pnas.93.21.11558
|View full text |Cite
|
Sign up to set email alerts
|

RNA replication by Q beta replicase: a working model.

Abstract: Two classes of RNA ligands that bound to separate, high affinity nucleic acid binding sites on Qj8 replicase were previously identified. RNA ligands to the two sites, referred to as site I and site II, were used to investigate the molecular mechanism of RNA replication employed by the four-subunit replicase. Replication inhibition by site I-and site 1I-specific ligands defined two subsets of replicatable RNAs. When provided with appropriate 3' ends, ligands to either site served as replication templates. UV cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 21 publications
2
62
0
Order By: Relevance
“…Qβ replicase is the most efficient in vitro system for nucleic acid amplification, far more efficient than PCR or isothermal amplification systems (17). However, the utilization of Qβ replicase for amplification of desired sequences has yet to be realized because of its puzzling and extraordinary template specificity requiring neither promoters nor primers (7,8). Although the described structure does not provide an immediate solution to this problem, it paves a way for a rational approach towards reaching this goal.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Qβ replicase is the most efficient in vitro system for nucleic acid amplification, far more efficient than PCR or isothermal amplification systems (17). However, the utilization of Qβ replicase for amplification of desired sequences has yet to be realized because of its puzzling and extraordinary template specificity requiring neither promoters nor primers (7,8). Although the described structure does not provide an immediate solution to this problem, it paves a way for a rational approach towards reaching this goal.…”
Section: Discussionmentioning
confidence: 96%
“…EF-Ts may stabilize EF-Tu in a conformation with affinity for Qβ RNA templates instead of aa-tRNAs (9). Ribosomal protein S1 mediates recognition of the Qβ plus strand (8), whereas the RNA chaperone Hfq is believed to mediate the access of the β-subunit to the 3′ end of the plus strand (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oleskina et al (1999) also identified ribosomal proteins that are associated with plastid DNA. Studies on phage Q replication demonstrated that S1 and the elongation factors EF-TU and EF-TS are also subunits of the b-RNA replicase (Brown and Gold, 1996). Likewise, EF-Tu, S3, L12, and L29 could have a dual function in plastid gene expression in that they coordinate replication, transcription, and translation.…”
Section: Discussionmentioning
confidence: 99%
“…The interspersed U residues were designed to prevent the replicase slippage anticipated on longer A tracts. As well as testing a role for C clusters as nonspecific transcriptional enhancers, these RNAs permitted testing a role for a short C cluster at an appropriate spacing upstream of the 3Ј-initiation box in enhancing transcription (proposed in reference 18), perhaps by binding to so-called Site II of the EF-Tu subunit (8).…”
Section: Resultsmentioning
confidence: 99%